Interactive infographic using Genially / Norul Fadhilah Ismail and Mahfuzah Mahayadin - Ismail, Norul Fadhilah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Genially is an online tool that offers an interactive presentation to create, animate or visualize the course materials using an available template such as presentations, video presentations, infographics, posters, quizzes, and gamification. It has been used in creating interactive educational resources (Enciso & Zelaya, 2021).